ON SINGULAR VARIETIES ASSOCIATED TO A POLYNOMIAL MAPPING FROM C-n TO Cn-1 - Nguyen Thi Bich Thuy [UNESP]; Ruas, Maria Aparecida Soares (Int Press Boston, Inc, 2018)
We construct singular varieties V-G associated to a polynomial mapping G : C-n -> Cn-1 where n >= 2. Let G : C-3 -> C-2 be a local submersion, we prove that if the homology or the intersection homology with total perversity (with compact supports or closed supports) in dimension two of any variety V-G is trivial then G is a fibration. In the case of a local submersion G : C-n -> Cn-1 where n >= 4, the result is still true with an additional condition.
Keywords: Complex polynomial mappings; intersection homology; singularities at infinity